Prevalence of fetal alcohol spectrum disorder among special subpopulations: a systematic review and meta‐analysis. (29th April 2019) - Popova, Svetlana; Lange, Shannon; Shield, Kevin; Burd, Larry; Rehm, Jürgen
Abstract: Aim: To collate prevalence estimates of fetal alcohol spectrum disorder (FASD) among special subpopulations (defined by service use). Design: Systematic literature review and meta‐analysis of original, quantitative studies published between 1 November 1973 and 1 December 2018. The PRISMAGATHER were adhered to. The review protocol [includes FASD prevalence in (a) general and (b) special populations] is available on PROSPERO (registration number: CRD42016033837). Prevalence estimates were collated for all included studies with country‐, disorder‐ [FASD and fetal alcohol syndrome (FAS)] and population‐specific random‐effects meta‐analyses conducted. Setting and Participants: A number of service‐defined subpopulations globally (see Findings). Measurements: The main outcome was the prevalence of FASD among special subpopulations. The critical appraisal of each study was conducted using the Joanna Briggs Institute tool. Findings: We identified 69 studies, comprising 6177 individuals diagnosed with FASD from 17 countries: Australia ( n  = 5), Brazil ( n  = 2), Canada ( n  = 15), Chile ( n  = 4), eastern Europe (Moldova, Romania and Ukraine; n  = 1), Germany ( n  = 1), Israel ( n  = 1), Lithuania ( n  = 1), the Netherlands ( n  = 1), Poland ( n  = 1), Russia ( n  = 9), South Korea ( n  = 1), Spain ( n  = 1), Sweden ( n  = 1) and United States ( n  = 25). FAS and FASD prevalence rates were collated for the following five subpopulations: children in care, correctional, special education, specialized clinical and Aboriginal populations. The estimated prevalence of FASD in these special subpopulations was 10–40 times higher compared with the 7.7 per 1000 (95% confidence interval = 4.9–11.7) global FASD prevalence in the general population. Conclusions: Global subpopulations of children in care, correctional, special education, specialized clinical and Aboriginal populations have a significantly higher prevalence of fetal alcohol spectrum disorder compared with the general population, which poses a substantial global health problem.